Geometric Morphometric Study on Geographic Dimorphism of Codling Moth Cydia pomonella (Lepidoptera, Tortricidae) from North West of Iran - Khaghaninia, S.; Mohammadi, S.A.; Irani Nejad, K.H.; Zahiri, R. (Вестник зоологии, 2011)
During years 2003—2004, nine geographical populations of codling moth Cydia pomonella (Linnaeus) from 4 north western provinces of Iran were collected.